Efficacy and Safety of Immune Checkpoint Inhibitor in Advanced Esophageal Squamous Cell Carcinoma: A Meta-Analysis - Gu, Yi-Min; Shang, Qi-Xin; Zhuo, Yue; Zhou, Jian-Feng; Liu, Bo-Wei; Wang, Wen-Ping; Che, Guo-Wei; Chen, Long-Qi (Frontiers in Oncology, 2021)
Background: The published evidence from several randomized controlled clinical trials of immunotherapy for advanced esophageal squamous cell carcinoma has shown promising results. This study aimed to investigate the efficacy and safety of immune checkpoint inhibitor treatment in esophageal squamous cell carcinoma. Methods: PubMed, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles published before December 30, 2020. The data for efficacy and safety of immune checkpoint inhibitor treatment were subjected to meta-analysis. Results: Seven clinical trials comprising 1733 patients were included. The results showed that immune checkpoint inhibitor treatment as second- or later-line treatment was associated with an increased risk of the objective response rate (relative risk: 1.82, 95% confidence interval: 0.82–4.04; P=0.002) and median overall survival (hazard ratio: 0.75, 95% confidence interval: 0.67–0.85; P<0.001) compared with chemotherapy in locally advanced or metastatic esophageal squamous cell carcinoma. Moreover, immune checkpoint inhibitor treatment was associated with significant improvement in median overall survival (hazard ratio: 0.61, 95% confidence interval: 0.48–0.77, P<0.001) compared with chemotherapy in the programmed death-ligand 1 (PD-L1)-positive population. However, immune checkpoint inhibitor treatment was also effective in all patients independent of PD-L1 expression. The most common grade 3 treatment-related adverse events with immune checkpoint inhibitor therapy were anemia, asthenia, rash, fatigue, decreased appetite, diarrhea, pneumonia, decreased neutrophil count, and vomiting. Patients undergoing immune checkpoint inhibitor therapy was associated with a decreased risk of treatment-related adverse events (relative risk: 0.82, 95% confidence interval: 0.62–1.08; P<0.001) and grade 3 treatment-related adverse events (relative risk: 0.50, 95% confidence interval: 0.42–0.60; P<0.001) compared with those undergoing chemotherapy. Conclusions: Immune checkpoint inhibitors as second- or later-line therapy may improve overall response rate and overall survival but not all oncological outcomes for patients with locally advanced or metastatic esophageal squamous cell carcinoma. Patients treated with immune checkpoint inhibitors might experience fewer treatment-related adverse events of any grade, but specifically grade 3, compared with those treated with chemotherapy.